“KAPATA PANAS PELA” NEGERI ARIATE DAN KATAPANG: TINJAUAN STRUKTUR DAN MAKNA - Taufik Taufik; A. Yusdianti T. (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Kapata panas pela Negeri Ariate and Katapang began to be forgotten by the two pela communities. This study aims to describe the opening structure, content, closing, and revealing the meaning. This research is qualitative descriptive field research. This research is located in Ariate and Katapang. Data was collected by interviewing traditional elders from Ariate and Katapang state and assisted with record and note techniques. The data is described through four stages, namely identification, classification, analysis, and conclusion. The results of the study show that form the kapata panas pela of the Ariate and Katapang consists of two parts. Each part is owned by each pela which consists of five stanzas and four lines. In total, the kapata panas pela consists of ten stanzas, four hundred lines. There are five codes in the structure of the kapata, namely hermeneutics, semics, proaretic symbols, and gnomics. The meaning of the kapata in the opening section is marked by greetings from the Pela Ariate state to the pela Katapang state which indicates that both Pela are holding an activity, namely the Panas Pela. The contents of the kapata contain the values ​​of brotherhood between two different ethnicities, religions, and cultures. The closing section of the Kapata is marked by a phrase from the land of Katapang which invites to enter the country of Ariate and hopes that God will always give blessings to both pela.